Why TEI Stand-off Markup Authoring Needs Simplification - Raffaele Viglianti (Journal of the Text Encoding Initiative)
Stand-off techniques are well documented in the TEI Guidelines and their use is encouraged. They are not widely adopted, however, except in their simplest forms, because they introduce considerable managerial overhead to a project’s workflow. This article argues that stand-off markup is becoming increasingly relevant to a wider range of TEI projects, partly due to recent developments in the theory of textual modeling that strongly acknowledge the multidimensional nature of text. As a consequence, there is a need to considerably simplify the authoring, management, and processing of stand-off markup; but to what extent is this possible? Can tools make stand-off techniques more approachable without substantially disrupting workflows familiar to TEI encoders? This article focuses on the complexities of stand-off markup authoring through two examples, one from the now completed project Freischütz Digital and one from ongoing development at the Shelley-Godwin Archive. More specifically, these examples present situations in which stand-off has been essential for bridging competing editorial representations of text, an operation that is becoming fundamental in the multidimensional modeling of text. The coreBuilder, an open source web-based visual environment for authoring stand-off markup, was created to aid the encoding workflow for these TEI projects. coreBuilder was awarded the first Rahtz Prize for TEI Ingenuity in 2017. The tool is presented here as an example of simplifying the creation of stand-off markup without hiding the XML from the expert encoder.